2013
DOI: 10.1371/journal.pgen.1003559
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of the Novel norpAP24 Suppressor, diehard4, in the Endo-lysosomal Trafficking Underlies Photoreceptor Cell Degeneration

Abstract: Rhodopsin has been used as a prototype system to investigate G protein-coupled receptor (GPCR) internalization and endocytic sorting mechanisms. Failure of rhodopsin recycling upon light activation results in various degenerative retinal diseases. Accumulation of internalized rhodopsin in late endosomes and the impairment of its lysosomal degradation are associated with unregulated cell death that occurs in dystrophies. However, the molecular basis of rhodopsin accumulation remains elusive. We found that the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…; Lee et al . ). Beyond these sequence‐based predictions, Osi6 , Osi7 and Osi8, all remain functionally uncharacterized.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…; Lee et al . ). Beyond these sequence‐based predictions, Osi6 , Osi7 and Osi8, all remain functionally uncharacterized.…”
Section: Resultsmentioning
confidence: 97%
“…; Lee et al . ). The only member of this gene family that has been functionally characterized is Osi21, and a recent study found that diehard4, a norpA P24 suppressor, is encoded by Osi21 (Lee et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Yassin et al () conducted a population genomics scan between an island specialist population of D. yakuba that recently specialized on Morinda citrifolia and a mainland generalist population of the same species and found that one of the strongest differentiation peaks mapped to the Osiris cluster on chromosome 3R (Yassin et al, ) possibly illustrating a case of parallel evolution through this locus. Only one other Osiris gene, Osi21 , has been functionally tested in D. melanogaster and loss‐of‐function alleles of this gene shift membrane balance between late endosomes and lysosomes facilitating degradation of endocytosed rhodopsin in eye cells (Lee, Song, & Hong, ). This finding is interesting as it suggests Osiris genes may be involved in detoxification.…”
Section: Introductionmentioning
confidence: 99%